Sex-Specific Association of Ambient Temperature With Urine Biomarkers in Southwest Coastal Bangladesh - Mazumder, Hoimonty; Mondol, Momenul Haque; Rahman, Mahbubur; Khan, Rizwana; Doza, Solaiman; Unicomb, Leanne; Jahan, Farjana; Mukhopadhyay, Ayesha; Makris, Konstantinos C.; Caban-Martinez, Alberto; Iqbal, Romaina; Ahmed, Faruk; et al. (My University, 2024)
Introduction: Men are vulnerable to ambient heat-related kidney disease burden; however, limited evidence exists on how vulnerable women are when exposed to high ambient heat. We evaluated the sex-specific association between ambient temperature and urine electrolytes, and 24-hour urine total protein, and volume. Methods: We pooled a longitudinal 5624 person-visits data of 1175 participants' concentration and 24-hour excretion of urine electrolytes and other biomarkers (24-hour urine total protein and volume) from southwest coastal Bangladesh (Khulna, Satkhira, and Mongla districts) during November 2016 to April 2017. We then spatiotemporally linked ambient temperature data from local weather stations to participants' health outcomes. For evaluating the relationships between average ambient temperature and urine electrolytes and other biomarkers, we plotted confounder-adjusted restricted cubic spline (RCS) plots using participant-level, household-level, and community-level random intercepts. We then used piece-wise linear mixed-effects models for different ambient temperature segments determined by inflection points in RCS plots and reported the maximum likelihood estimates and cluster robust standard errors. By applying interaction terms for sex and ambient temperature, we determined the overall significance using the Wald test. Bonferroni correction was used for multiple comparisons. Results: The RCS plots demonstrated nonlinear associations between ambient heat and urine biomarkers for males and females. Piecewise linear mixed-effects models suggested that sex did not modify the relationship of ambient temperature with any of the urine parameters after Bonferroni correction (P < 0.004). Conclusion: Our findings suggest that women are as susceptible to the effects of high ambient temperature exposure as men.
Keywords: GeoHealth; climate and health; environment; environmental determinants of health; planetary health; renal elimination